2019
DOI: 10.3390/biom9080369
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Modifications in NETosis and NETs-Mediated Diseases

Abstract: : Neutrophils undergo a unique form of cell death that generates neutrophil extracellular traps (NETs) that may help to neutralize invading pathogens and restore homeostasis. However, uncontrolled NET formation (NETosis) can result in numerous diseases that adversely affect health. Recent studies further elucidate the mechanistic details of the different forms of NETosis and their common end structure, as NETs were constantly found to contain DNA, modified histones and cytotoxic enzymes. In fact, emerging evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 207 publications
(270 reference statements)
1
58
0
1
Order By: Relevance
“…Interestingly, a similar EV-mediated export of deiminated histones, as observed in cow serum-EVs in the current study, was recently identified in the naked mole-rat, an animal with unusual immunological and metabolic traits [98], as well as in alligator, also an animal with unusual antimicrobial, including anti-viral responses [93]. Deiminated histone H3 is commonly used as an indicator for neutrophil extracellular trap formation (NETosis) [31,244], which has been related to PAD4 and implicated in anti-viral responses in cattle respiratory syncytial virus disease [42], in response to parasitic infections in cattle [245][246][247] as well as in response to certain antibiotics [248]. Interestingly, in crocodilians, extracellular histones H2A and H4 have been identified to act as inhibitors of viral (HIV) infection in vitro [249], although roles for post-translational deimination were not assessed.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, a similar EV-mediated export of deiminated histones, as observed in cow serum-EVs in the current study, was recently identified in the naked mole-rat, an animal with unusual immunological and metabolic traits [98], as well as in alligator, also an animal with unusual antimicrobial, including anti-viral responses [93]. Deiminated histone H3 is commonly used as an indicator for neutrophil extracellular trap formation (NETosis) [31,244], which has been related to PAD4 and implicated in anti-viral responses in cattle respiratory syncytial virus disease [42], in response to parasitic infections in cattle [245][246][247] as well as in response to certain antibiotics [248]. Interestingly, in crocodilians, extracellular histones H2A and H4 have been identified to act as inhibitors of viral (HIV) infection in vitro [249], although roles for post-translational deimination were not assessed.…”
Section: Discussionsupporting
confidence: 80%
“…In this study we observed decreased levels of antimicrobial peptides, MPO and LL37 in T1D NETs and additionally uncovered a strong shift toward histone-associated DNA fragments compared to healthy NETs. Particular histone modifications are an increasingly recognized quality of NETs influencing both the process of NET release itself and NET effect on numerous diseases (39), and observed differences in NET composition in T1D patients might strongly influence their biological activity, including their contribution to T1D development and progression. Since NETs in general are a source of autoantigens (40) they may contain islet autoantigens in T1D patients, which in turn would be processed by dendritic cells and further elicit both specific B cell and T cell responses (41).…”
Section: Discussionmentioning
confidence: 99%
“…When neutrophils are stimulated by NETotic inducers such as lipopolysaccharide (LPS) or polymethylmethacrylate (PMA), Nox-dependent NET formation is induced [ 137 ]. Studies have reported that these agonists (LPS and PMA) induce Nox-dependent NET formation through two different mechanisms.…”
Section: Neutrophil Extracellular Traps (Nets)mentioning
confidence: 99%
“…During NOX-derived ROS production optimal environment is created for NE and MPO [ 137 ]. These enzymes which are normally contained within azurophilic granules are now free to interact with the nucleus where they may cleave histones and facilitate chromatin decondensation [ 160 ].…”
Section: Neutrophil Extracellular Traps (Nets)mentioning
confidence: 99%